Dopamine and Noradrenaline in the Brain; Overlapping or Dissociate Functions? - Ranjbar-Slamloo, Yadollah; Fazlali, Zeinab (Frontiers in Molecular Neuroscience, 2020)
Dopamine and noradrenaline are crucial neuromodulators controlling brain states, vigilance, action, reward, learning and memory processes. Ventral tegmental area (VTA) and Locus Coeruleus (LC) are canonically described as the main sources of dopamine (DA) and noradrenaline (NA) with dissociate functions. A comparison of diverse studies shows that these neuromodulators largely overlap in multiple domains such as shared biosynthetic pathway and co-release from the LC terminals, convergent innervations, non-specificity of receptors and transporters and shared intracellular signalling pathways. DA-NA interactions are mainly studied in prefrontal cortex and hippocampus, yet it can be extended to the whole brain given the diversity of catecholamine innervations. LC can simultaneously broadcast both dopamine and noradrenaline across the brain. Here, we briefly review the molecular, cellular and physiological overlaps between DA and NA systems and point to their functional implications. We suggest that DA and NA may function in parallel to facilitate learning and maintain the states required for normal cognitive processes. Various signalling modules of NA and DA have been targeted for developing of therapeutics. Understanding overlaps of the two systems is crucial for more effective interventions in a range of neuropsychiatric conditions.